(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
In the present study, the clinical outcome of mineral trioxide aggregate and Biodentine as repairing materials in the management of pulpal floor perforation was compared in vivo. Thirty teeth having pulpal floor perforation were enrolled in this study, out of which 15 perforations were repaired with mineral trioxide aggregate and the remaining 15 were subjected to Biodentine treatment. Following perforation repair, each tooth was then subjected to root canal therapy. Patients were recalled at 3, 6 and 12 month interval. The assessment of pain, pain on palpation, tenderness on percussion, and radiological evaluation was performed to determine the repair ability of pulpal floor perforation. Statistical analysis was performed with Chi-square test between the two groups and a value of p<0.05 was considered as statistically significant. The results showed that pain, tenderness on percussion as well as the thickness of periodontal ligament was gradually decreased and the communication between the perforation and oral cavity was successfully repaired following MTA and Biodentine therapy. Furthermore, the differences between MTA and Biodentine were not statistically significant. It can be concluded that clinical outcome and repair of pulpal floor perforation by Biodentine is almost similar to MTA.